Nap Practices and Social–Emotional Development in Early Childhood: Evidence from a Daycare Setting - Salsabila, Annida; Jayadinata, Asep Kurnia; Ardiyanti, Dhea; Mustafa, Lily Muliana (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to describe the dynamics of changes in children’s social–emotional functioning before and after napping in early childhood education institutions that provide childcare services. Employing a qualitative approach with a descriptive case study design, the study investigates children’s behavioral patterns in a naturalistic setting through observations and semi-structured interviews. The participants comprised three children (two typically developing and one with special needs) along with three accompanying teachers, selected using convenience total sampling technique due to their availability at the research site. Data were analyzed using thematic analysis encompassing open coding, axial coding, and selective coding procedures. The findings identified three major themes: first, a significant improvement was observed in emotional regulation, autonomy, and social interaction following nap time. Second, substantial individual variations emerged, particularly in the child with special needs, who required more intensive co-regulation support. Third, the nap time experience was influenced by multifactorial interactions, including daily routines, physical environment, caregiver support, and parent, educator communication. These findings reinforce our understanding of emotional regulation, socio-emotional competence, and executive functioning in child development. The present study offers practical implications for policies regarding flexible nap time arrangements in full-day or daycare early childhood education settings and is aligned with SDG 3 (mental health and well-being) and SDG 4.2 (access to quality early childhood education).